2003
DOI: 10.1007/s00701-003-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife radiosurgery for metastatic tumours in the brain stem

Abstract: GKS for brain stem metastases using a marginal dose of 15 Gy or less is effective and relatively safe. Accurate targeting of the tumour and safe dose planning are essential to obtain satisfactory results with GKS for brain stem metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
4
38
0
Order By: Relevance
“…This potential for morbitiy coupled with a concern regarding possible increased radiosensitivity of brainstem tissue this has led to the exclusion of brainstem metastases from various radiosurgery clinical trials [3][4][5]. Data on the safety and efficacy of stereotactic radiosurgery in the management of brainstem metastases is lacking therefore, and relies on retrospective reports from single institutions [6][7][8][9][10][11][12][13][14]. Nine previous reports have been published.…”
Section: Introductionmentioning
confidence: 96%
“…This potential for morbitiy coupled with a concern regarding possible increased radiosensitivity of brainstem tissue this has led to the exclusion of brainstem metastases from various radiosurgery clinical trials [3][4][5]. Data on the safety and efficacy of stereotactic radiosurgery in the management of brainstem metastases is lacking therefore, and relies on retrospective reports from single institutions [6][7][8][9][10][11][12][13][14]. Nine previous reports have been published.…”
Section: Introductionmentioning
confidence: 96%
“…
small case series for the management of brainstem metastases using Gamma Knife Radiosurgery (GKRS) 12,16,18,22,26,35) . The present study assessed outcomes following our use of GKRS for the management of brainstem metastasis, and we investigated the effect of treatment on tumor size and survival time.
MATERIALS AND METHODS
Patient characteristics

From November 1992 to June 2010, a total of 32 patients underwent GKRS for local control of brainstem metastasis at our institute.

…”
mentioning
confidence: 99%
“…16,17 All of these studies have shown that SRS is a safe, reliable, and efficient treatment method for brainstem metastases. [3][4][5][6][13][14][15][16][17] This study differs from others in reporting treatment results of not only metastases in the brainstem but also those that are adjacent to brainstem (≤5 mm) and using CyberKnife as an FSRT/ SRS system. The CyberKnife SRT system has certain improved features of utility compared to the Gamma Knife radiosurgery system.…”
Section: Discussionmentioning
confidence: 82%
“…In the current literature, most of the studies have used Gamma Knife for the treatment of brainstem metastases using stereotactic radiosurgery. 3,5,6,[13][14][15] In addition, there are other studies in which linac-based systems were used as a means of SRS. 16,17 All of these studies have shown that SRS is a safe, reliable, and efficient treatment method for brainstem metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation